2016
DOI: 10.1016/j.jcin.2016.08.035
|View full text |Cite
|
Sign up to set email alerts
|

Pre-Existing Right Bundle Branch Block Increases Risk for Death After Transcatheter Aortic Valve Replacement With a Balloon-Expandable Valve

Abstract: Patients with RBBB demonstrated an increased risk for cardiovascular mortality after TAVR, and patients with RBBB and without pacemakers were at higher risk for cardiac death early after discharge. Patients with prior RBBB should be carefully monitored after undergoing TAVR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
53
2
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 82 publications
(60 citation statements)
references
References 29 publications
1
53
2
2
Order By: Relevance
“…In this retrospective analysis, we obtained data from October 2013 to July 2016, using the Optimized transCathEter vAlvular intervention (OCEAN) TAVI registry . The OCEAN‐TAVI is a prospective, multicenter, observational registry of symptomatic patients with severe aortic valve stenosis (AS) undergoing TAVR at 14 collaborating hospitals located in Japan.…”
Section: Methodsmentioning
confidence: 99%
“…In this retrospective analysis, we obtained data from October 2013 to July 2016, using the Optimized transCathEter vAlvular intervention (OCEAN) TAVI registry . The OCEAN‐TAVI is a prospective, multicenter, observational registry of symptomatic patients with severe aortic valve stenosis (AS) undergoing TAVR at 14 collaborating hospitals located in Japan.…”
Section: Methodsmentioning
confidence: 99%
“…Younger patients included in this cohort had fewer pre‐existing RBBB, which might be the reason why the presence of RBBB was not significantly different in the PPI group. Being considered as a dominant predictor of PPI, RBBB has also been found to be associated with increased all‐cause and cardiovascular mortality post‐TAVR . Thus, patients with pre‐existing RBBB still need careful surveillance after the procedure.…”
Section: Discussionmentioning
confidence: 99%
“…We advocate early discharge with leadless temporary pacemaker and continuous monitoring in high risk patients with widening QRS interval and new LBBB post procedure (57). We also recommend very close follow up in patients who had RBBB at baseline on pre-procedure EKG but did not require PPM implantation after TAVR, as recent studies have shown an increase in mortality in these patients due to latent CHB and/or sudden cardiac death (58,59).…”
Section: Post Procedures Recommendationsmentioning
confidence: 96%